PENDIDIKAN DALAM DINAMIKA KEBUDAYAAN MENCIPTAKAN MANUSIA YANG BERKARAKTER POSITIF - Dewi, Nurmala (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
In creating human beings capable of thinking and acting with global insight and being able to appreciate diversity so as to lead a nation of character that can support the development of the nation and build the identity of a nation, the school is instrumental in shaping the character of the nation. This study is about the role of education in schools in the cultural dynamics that exist in the school MTs Negeri 2 Palembang City which aims to form human beings who have a positive character that can compete. This research use qualitative method with field research, data taken by doing observation directly to research object. Based on the results of direct observation of the researchers turned out that the activities of habituation performed at the school MTs Negeri 2 Palembang City can grow or form the character of students who are responsible, disciplined, tolerant, have religious spirit, morals, honest, sportsmanship and become a better person Keywords— Education, Cultural Dynamics, Positive Character